2023
DOI: 10.2196/41804
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Mobile-Based Intervention for Parents of Children With Crying, Sleeping, and Feeding Problems: Randomized Controlled Trial

Abstract: Background Excessive crying, sleeping, and feeding problems in early childhood are major stressors that can result in parents feeling socially isolated and having low self-efficacy. Affected children are a risk group for being maltreated and developing emotional and behavioral problems. Thus, the development of an innovative and interactive psychoeducational app for parents of children with crying, sleeping, and feeding problems may provide low-threshold access to scientifically based information a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…Theoretical models argue that persistent RPs or clinically relevant disorders such as sleep onset or night waking disorder or excessive crying disorder (24) are best described and understood in a relational context: They are frequently embedded in a family system with high psychosocial stress and problems in the parent-child relationship/interaction (2). Indeed, studies showed that having an infant suffering from RPs puts parents under enormous stress (9,25). Moreover, parents of infants with RPs report lower levels of self-efficacy, more social isolation (2,26,27) and more symptoms of depression and anxiety (28, 29).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical models argue that persistent RPs or clinically relevant disorders such as sleep onset or night waking disorder or excessive crying disorder (24) are best described and understood in a relational context: They are frequently embedded in a family system with high psychosocial stress and problems in the parent-child relationship/interaction (2). Indeed, studies showed that having an infant suffering from RPs puts parents under enormous stress (9,25). Moreover, parents of infants with RPs report lower levels of self-efficacy, more social isolation (2,26,27) and more symptoms of depression and anxiety (28, 29).…”
Section: Introductionmentioning
confidence: 99%
“…Also, infants with RPs tend to show more difficult temperamental features, such as fussiness (66) and negative emotionality (28). Moreover, it is well known that high stress, which is common in parents of infants with RPs (2,25), is likely to lead to a break-down of mentalizing abilities (67). Caregivers of infants with RPs might also be inconsistently attuned to infants, comparable to caregivers of children with a resistant attachment style (41).…”
Section: Introductionmentioning
confidence: 99%